Cilostazol for intermittent claudication - Bedenis, Rachel (Cochrane Database Syst Rev, 2014)
BACKGROUND: Peripheral arterial disease (PAD) affects between 4% and 12% of people aged 55 to 70 years, and 20% of people over 70 years. A common complaint is intermittent claudication, characterised by pain in the legs or buttocks that occurs with exercise and which subsides with rest. Compared with age‐matched controls, people with intermittent claudication have a three‐ to six‐fold increase in cardiovascular mortality. Symptoms of intermittent claudication, walking distance, and quality of life can be improved by risk factor modification, smoking cessation, and a structured exercise programme. Antiplatelet treatment is beneficial in patients with intermittent claudication for the reduction of vascular events but has not previously been shown to influence claudication distance. This is an update of a review first published in 2007. OBJECTIVES: To determine the effect of cilostazol (an antiplatelet treatment) on improving initial and absolute claudication distances, and in reducing mortality and vascular events in patients with stable intermittent claudication. SEARCH METHODS: For this update, the Cochrane Peripheral Vascular Diseases Group Trials Search Co‐ordinator searched the Specialised Register (last searched October 2013) and CENTRAL (2013, Issue 9). SELECTION CRITERIA: Double‐blind, randomised controlled trials (RCTs) of cilostazol versus placebo, or versus other antiplatelet agents in patients with stable intermittent claudication. DATA COLLECTION AND ANALYSIS: Two authors independently assessed trials for selection and independently extracted data. Disagreements were resolved by discussion. We performed the meta‐analysis as a fixed‐effect model with weighted mean differences (WMDs) and 95% confidence intervals (CIs) for continuous data, and odds ratios (ORs) with 95% CIs for dichotomous data. MAIN RESULTS: We included fifteen double‐blind, RCTs comparing cilostazol with placebo, or medications currently known to increase walking distance e.g. pentoxifylline. There were a total of 3718 randomised participants with treatment durations ranging from six to 26 weeks. All participants had intermittent claudication secondary to PAD. Comparisons included cilostazol twice daily, with dosages of 50 mg, 100 mg and 150 mg compared with placebo, and cilostazol 100 mg, twice daily, compared with pentoxifylline 400 mg, three times daily. The methodological quality of the trials was generally low, with the majority being at an unclear risk for selection bias, performance bias, detection bias and other bias. Attrition bias was generally low, but reporting bias was high or unclear in the majority of the studies. For eight studies data were compatible for comparison by meta‐analysis, but data for seven studies were too heterogenous to be pooled. For the studies included in the meta‐analysis, for initial claudication distance (ICD ‐ the distance walked on a treadmill before the onset of calf pain) there was an improvement in the cilostazol group for the 100 mg and 50 mg twice daily, compared with placebo (WMD 31.41 metres, 95% CI 22.38 to 40.45 metres; P < 0.00001) and WMD 19.89 metres, 95% CI 9.44 to 30.34 metres; P = 0.0002), respectively. ICD was improved in the cilostazol group for the comparison of cilostazol 150 mg versus placebo and cilostazol 100 mg versus pentoxifylline, but only single studies were used for these analyses. Absolute claudication distance (ACD ‐ the maximum distance walked on a treadmill) was significantly increased in participants taking cilostazol 100 mg and 50 mg twice daily, compared with placebo (WMD 43.12 metres, 95% CI 18.28 to 67.96 metres; P = 0.0007) and WMD 32.00 metres, 95% CI 14.17 to 49.83 metres; P = 0.0004), respectively. As with ICD, ACD was increased in participants taking cilostazol 150 mg versus placebo, but with only one study an association cannot be clearly determined. Two studies comparing cilostazol to pentoxifylline had opposing findings, resulting in an imprecise CI (WMD 13.42 metres (95% CI ‐43.51 to 70.35 metres; P = 0.64). Ankle brachial index (ABI) was lowered in the cilostazol 100 mg group compared with placebo (WMD 0.06, 95% CI 0.04 to 0.08; P < 0.00001). The single study evaluating ABI for the comparison of cilostazol versus pentoxifylline found no change in ABI. There was no association between treatment type and all‐cause mortality for any of the treatment comparisons, but there were very few events, and therefore larger, adequately powered studies will be needed to assess if there is a relationship. Only one study evaluated individual cardiovascular events, and from this study there is no clear evidence of a difference between any of the treatment groups and risk of myocardial infarction or stroke. We evaluated adverse side effects, and in general cilostazol was associated with a higher odds of headache, diarrhoea, abnormal stool, dizziness and palpitations. We only reported quality of life measures descriptively as there was insufficient statistical detail within the studies to combine the results, although there was a possible indication in improvement of quality of life in the cilostazol treatment groups. AUTHORS' CONCLUSIONS: Cilostazol has been shown to be of benefit in improving walking distance in people with intermittent claudication secondary to PAD. Although there is an increase in adverse side effects, they are generally mild and treatable. There is currently insufficient data on whether taking cilostazol results in a reduction of all‐cause mortality and cardiovascular events or an improvement in quality of life. Future research into the effect of cilostazol on intermittent claudication should carefully consider comparability, sample size and homogeneity when designing a study.